THE CORRELATION ACTIVITY OF FARMER GROUP MEMBERS TO FARMER INCOME IN SOAK BATOK VILLAGE, NORTH INDRALAYA DISTRICT, OGAN ILIR REGENCY: THE CORRELATION ACTIVITY OF FARMER GROUP MEMBERS TO FARMER INCOME IN SOAK BATOK VILLAGE, NORTH INDRALAYA DISTRICT, OGAN ILIR REGENCY - Muhammad Arbi; Idham Alamsyah (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2020)
Abstract: The objectives of the study are (1) Analyzing the Activity of Farmer Groups in Soak Batok Village, North Indralaya District, Ogan Ilir Regency, (2) To calculate the amount of farmer rice farming income in the Soak Batok Village, North Indralaya District, Ogan Ilir Regency, (3) For analyze the relationship between the level of activeness of farmer group members to the income of farmers in the lowland rice farming in Soak Batok Village, North Indralaya District, Ogan Ilir Regency. In this research, the method used is the survey method. Sampling was carried out by Stratified Random Sampling method by taking 40 farmers from a population of 385 populations. The results showed that the level activity members of the Farmer Group are 6.50 classified in the active category. The total income of farmer paddy farmers there is a difference in income, namely for the good category of farmer groups amounting to Rp30,278,067.53 while for the Farmer groups the category of less good is Rp26,726,411.00. There is relationship of significant the level of activity of farmer group members to the income of farmers. Keyword: Farmer Group Activeness, Revenue